Outcomes of Myomectomy at the Time of Cesarean Section among Pregnant Women with Uterine Fibroids: A Retrospective Cohort Study. (10th March 2019) - Zhao, Rong; Wang, Xin; Zou, Liying; Zhang, Weiyuan
Abstract : Objective . A retrospective study was performed to evaluate the safety and feasibility of cesarean myomectomy among pregnant women with uterine fibroids (UFs). Methods . Upon data collection, the pregnant women with UF underwent cesarean section in the 39 hospital divided into two groups: cesarean myomectomy group, receiving cesarean section and myomectomy; cesarean group, receiving cesarean section only. Information about the type, location, and number of UFs was collected from the medical records or the prenatal ultrasound examinations. Results . In the cesarean myomectomy group, the proportion of subserous UFs was significantly higher than the cesarean group (65.6% versus 49.3%, P < 0.0001). The comparison of postpartum hemorrhage, neonatal weight, fetal distress, and neonatal asphyxia showed no statistical significance. Multivariate logistic regression analysis demonstrated that birth weight ≥4000 g (OR 3.1, 95% CI:1.6–6.0) and presence of diameter > 5 cm fibroids (OR 2.2, 95%CI:1.3–4.0) were high risk factors for PPH ≥1, 000 ml. Conclusions . Myomectomy during cesarean section was a common procedure in mainland China. Myomectomy cesarean could be safe and feasible based on the estimation by experienced obstetricians. During the procedure, special attention should be paid to a large-sized leiomyoma ≥5cm and birth weight ≥4, 000 g.